VD_FINDINFO HC / 2012 / 98 vom 19. Januar 2012 - VD Tribunal cantonal (2012)
ASSURANCE DE RESPONSABILITÉ CIVILE, DOMMAGE, RENTE SIMPLE D'INVALIDITÉ, PRÉDISPOSITION | 41 CO, 42 CO, 43 CO, 47 CO, 58 LCR